2015
DOI: 10.1186/s40478-015-0237-8
|View full text |Cite
|
Sign up to set email alerts
|

Tau phosphorylation regulates the interaction between BIN1’s SH3 domain and Tau’s proline-rich domain

Abstract: IntroductionThe application of high-throughput genomic approaches has revealed 24 novel risk loci for Alzheimer’s disease (AD). We recently reported that the bridging integrator 1 (BIN1) risk gene is linked to Tau pathology.ResultsWe used glutathione S-transferase pull-down assays and nuclear magnetic resonance (NMR) experiments to demonstrate that BIN1 and Tau proteins interact directly and then map the interaction between BIN1’s SH3 domain and Tau’s proline-rich domain (PRD) . Our NMR data showed that Tau ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(108 citation statements)
references
References 32 publications
10
95
0
Order By: Relevance
“…Direct interactions between tau and SH3-containing proteins have been reported [36, 273, 278, 411, 462, 483] and these interactions are likely to have roles in modulating the signalling functions of tau. Additionally, signalling roles have been postulated from the identification of phosphatidylinositol and phosphatidylinositol bisphosphate as tau binding partners of the proline-rich domain [134, 468].…”
Section: Tau Structure and Functionmentioning
confidence: 99%
“…Direct interactions between tau and SH3-containing proteins have been reported [36, 273, 278, 411, 462, 483] and these interactions are likely to have roles in modulating the signalling functions of tau. Additionally, signalling roles have been postulated from the identification of phosphatidylinositol and phosphatidylinositol bisphosphate as tau binding partners of the proline-rich domain [134, 468].…”
Section: Tau Structure and Functionmentioning
confidence: 99%
“…In addition, in a Drosophila melanogaster model overexpressing Tau, bin1 homologue Amph mediates Tau toxicity [11,16], and an increase in bin1 expression is observed in AD [11]. In line with Tau, it has been suggested that the BIN1-Tau complex could be at the interface between the actin and microtubule network and that its deregulation may impact neuronal function [12]. In line with Tau, it has been suggested that the BIN1-Tau complex could be at the interface between the actin and microtubule network and that its deregulation may impact neuronal function [12].…”
Section: Introductionmentioning
confidence: 98%
“…BIN1 has been described to directly interact with the Tau protein [11,12], using NMR spectroscopy with recombinant proteins, in vitro glutathion S-transferase (GST) pulldown from HEK293 lysates, polymerase ligation assays in primary neuronal culture [12], as well as reciprocal coimmunoprecipitations from wild-type mouse brain homogenates, which confirm interaction at the physiological level [11]. BIN1 has been described to directly interact with the Tau protein [11,12], using NMR spectroscopy with recombinant proteins, in vitro glutathion S-transferase (GST) pulldown from HEK293 lysates, polymerase ligation assays in primary neuronal culture [12], as well as reciprocal coimmunoprecipitations from wild-type mouse brain homogenates, which confirm interaction at the physiological level [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the role of BIN1 in myelination, BIN1 expression increases at the onset of postnatal brain myelination and during differentiation of cultured oligodendrocytes [105,106]. In contrast, the loss of BIN1 significantly correlates with the extent of demyelination in MS lesions [105,106]. BIN1 undergoes complex alternative splicing to generate multiple isoforms that have diverse functions [105,106].…”
Section: Tau In Oligodendrocytes and Cns Degenerative Diseasesmentioning
confidence: 84%